KONTEKSTUALISASI MAKNA DAN HAK-HAK PEREMPUAN DALAM ALQURAN - Mukarromah Mukarromah (PERADA, 2018)
Gender studies in Islam have always been concerned because many claims that religion, including Islam, is often accused of not being pro-women. This article wold like to the meaning of the Quranic term about women. In this study, there are many words in the Quran that refer to women. There are at least four words, namely nisa', mar'ah, untsa and banat. The first three word refer to adult women and have their own characteristics when they are used in verses. This maturity also has consequences for further studies because it creates the characteristics and categories for women themselves. Based on the character, it is said in the Qur'an that women are pious, hardworking, patient, loyal, rebellious, traitors, teasers and so on. Equally important, Quran only distinguishes women's and men's issues in natural matters. Whereas in other matters, women only get privileges like listing their degrees.